The creation and innovation of the Prophet’s companions - AL.Otibe, Manei Dabi (Journal of Humanities & Social Sciences, 2019)
The biography of Prophet Muhammad (Peace be Upon Him) is full of undiscovered treasures that need efforts of those who could search for and reveal its precious treasures. Through the historical approach, and by going through an introduction and four chapters, this study tried to reveal some aspects of its excellence by reviewing some of the attitudes that express creativity and innovation in directing and implementing matters in order to serve the religion of Islam in a variety of fields, including, but not limited to: the scientific, social, military, and economic fields. The researcher concluded that the Islamic Nation is the birth of creative people, and that Islam and the prophet Muhammad (PUH) embrace the thought, the deep thinking and the guided and useful creation that has no limits. Moreover, the events and their course of action mobilize those who are inclined to keep their minds off the usual thoughts in order to reach fruitful results that have achieved great and speed success, compared to traditional stereotypes that may not achieve such successes. The researcher recommended the need to read the Prophetic biography with an aesthetic and analysis reading in all its positions and events according to the mechanism of creativity and innovation.